COMPRATIVE ANTIMICROBIAL EFFICACY EVALUATION OF A NEW PRODUCT ELORES AGAINST MEROPENEM ON GRAM NEGATIVE ISOLATES - Kumar, Manoj; Chaudhary, Shikha; Makkar, Diljot Kumar; Garg, Neeru; Chugh, Sanjeevkumar (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Background and objective: Increased resistance of Gram-negative bacteria towards most of the available antibiotics, especially beta-lactam antibiotics is a prime difficulty for the treatment of infections caused by these pathogens. In view of the fact that there is a continuous increase in the antibitic resistance and the limited available therapeutic options, we aimed the present work to evaluate the antibiotic susceptibility pattern of 847 isolates towards meropenem and Elores (ceftriaxone+sulbcatam+and adjuvant ethylenediaminetetraacetic acid). Methods: A total of 1180 clinical samples were collected from patients suspected of bacterial infection between January 2014 to June 2014. These samples were subjected for bacterial identification. Antibiotic susceptibility testing were carried out according to the recommendations of Clinical Laboratory Standards Institute (CLSI) guidelines. Results: Among the samples which showed the presence of bacteria, around 29.04% samples were of sputum followed by urine and blood which contributed to 21.95% and 12.51%, respectively. Escherichia coli (39.55%) was found to be the most dominant pathogen, followed by Pseudomonas aeruginosa (19.12%), Klebsiella pneumoniae (12.39%), Proteus mirabilis (8.50%), Klebsiella oxytoca (8.26%), Acinetobacter baumannii (5.31%), Morganella morganii (3.77%), Serratia marcescens (2.24%). The susceptibility of Elores was comparable with meropenem in some of the organisms, but Elores displayed higher susceptibility in E. coli, A. baumannii, K. pneumoniae, P. mirabilis, K. oxytoca, M. morganii and S. mercescens which might be due to presence of metallo-beta lactamases in these isolates. Conclusion: Overall, the results of this study strongly advocate the equivalance of Elores with meropenem and can be of very effective alternative to treat against the deadly multi drug resistant Gram-negative bacteria. Keywords: Elores, Gram-negative bacteria, Nosocomial infections, Antimicrobial Resistance, Susceptibility.